Observations on the Pezzana-Panizzi correspondence kept at the Palatina Library in Parma - Marenghi, Paolo (Bibliothecae.it, 2023)
Panizzi, a student at the University of Parma, was a frequent visitor to the Palatine Library and there he met Angelo Pezzana. In a thorough analysis of the correspondence held between the two librarians, preserved today in the Parma library, emerged how much the relationship between them was based on great esteem, admiration and respectfulness,but also on common their historical-bibliographical interests and attention to the quality of the collections. The letters between the two, dating beck from 1838 to 1859, bear the witness of exchanges of volumes, personal favors and mutual requests for texts aimed at increasing their respective libraries. Panizzi and Pezzana shared the same passion for the historical- bibliographic culture but had a different conception of the bibliological and cataloging dimension. Most of the documents cited, described or transcribed here are inedited.